Development of Learning Media Using Articulate Storylines to Increase Student Motivation in Mathematics Subjects in Elementary Schools - Rafika Indra Julia; Nellitawati; Alwen Bentri; Desyandri (Postgraduate, University of Mataram, 2023)
The purpose of this research is to develop learning media based on articulate storylines that are used to increase elementary school students' learning motivation in learning Mathematics.Study This use research methods development (Research and Development or R&D). Research using model study Which adapted from development models ADDIE. This model uses 5 stages that is analysis stage, Design, Development, Implementation, and Evaluation. Study this is done in 3 schools namely SDN 18, SDN 24 and SDN 30 Payakumbuh City. Province Sumatra West. Data collection was carried out through product validation, interviews, observation, questionnaires, and documentation. Data analysis in this study is an analysis of product validity, product practicality and product effectiveness.The results of media validation get a value of 82%, from the validation of language experts get a value of 100%, from the validation of construct experts get a value of 95% and from the results of the material validator get a value of 87%. So that the results are 91% and with the description